Effects of statins on thrombosis development in patients with systemic lupus erythematosus and antiphospholipid antibodies. (February 2018) - Watanabe, T; Oku, K; Amengual, O; Hisada, R; Ohmura, K; Nakagawa, I; Shida, H; Bohgaki, T; Horita, T; Yasuda, S; Atsumi, T
The objective of this study is to identify the effects of statins and risk factors for thrombosis in patients with new onset of systemic lupus erythematosus (SLE) with or without antiphospholipid antibodies (aPL). Consecutive patients with SLE without history of thrombotic events were retrospectively enrolled from April 1997 to February 2014. The development of first thrombosis and death caused by thrombosis were defined as the study endpoint. Risk and protective factors for developing thrombosis were analyzed. A total of 152 patients, 80 positive and 72 negative for aPL, were included. In aPL-positive patients, 15 developed arterial ( n  = 6) and venous ( n  = 9) thrombosis (median follow-up period 69 months). Cox's proportional hazards model showed that older age at SLE onset and IgG-anticardiolipin antibodies (aCL) were statistically significant risks for thrombosis. Statin therapy was identified as a statistically significant protective factor against thrombosis (hazard ratio 0.12, 95% confidence interval 0.01–0.98). In aPL-negative patients (median follow-up period 46 months), seven patients developed thrombosis (five arterial and two venous). No risk factors for thrombosis were found in this group. In aPL-positive patients with SLE, the late disease onset and the presence of IgG-aCL represented additional risk factors for thrombosis. Statin treatment appeared as a protective factor for thrombosis.